Історія однієї помилки. (Внесок Я. Б. Епштейна на будівництво політехнічного інституту в Києві) - Андреєв, І. (Краєзнавство, 2018)
Проаналізовано матеріали, які стосуються збору коштів на будівництво Київського політехнічного інституту, а саме, великого внеску, зробленого власником банкірської контори Яковом Борисовичем Епштейном. Виявлені документи заперечують усталену в даний час думку про розподіл пожертв, які були зроблені меценатами на межі ХIХ–ХХ століть. Отримані висновки базуються, у першу чергу, на архівних матеріалах міста Києва. The materials related to the collection of funds for the construction of the Kyiv Polytechnic Institute, namely, the big contribution made by the owner of the bank’s office Yakov Borisovich Epshtein, were analyzed. It has been established that in the publications of modern researchers this donation considerably exceeds the amount that was actually deposited to the institute. An error in the amount of donations first appeared more than 100 years ago in the publication of the professor of the Kyiv Polytechnic Institute, Ivan Ganitsky. Reliable information was made public in 1902 by a direct participant in the collection of money, the secretary of the «Highest established committee to collect donations for the construction of the Kyiv Polytechnic Institute». The documents found deny the current opinion about the distribution of donations, which were made by patrons at the turn of the 19th–20th centuries. The directions of the business activity of J. B. Epstein in Kyiv are given. The findings are based, first of all, on the archival materials of the city of Kyiv.